Peer education program improved the knowledge and skills of adolescents regarding breast self-examination - Waliyanti, Ema; Nurul Arinandika , Kailifah (Universitas Aisyiyah Yogyakarta, 2024)
The prevalence of adolescents doing BSE in Indonesia is still low at 46.3%. This is because young women are still unfamiliar with BSE. Based on this, peer education needs to be implemented to increase teenagers' knowledge and skills related to BSE through peers. This study aims to determine the effectiveness of peer education in improving adolescents' knowledge and skills regarding breast self-examination. This research uses a Quasi-experimental method with a control group design. The research respondents were 36 teenagers who were divided into 18 intervention groups and 18 controls. The sampling method used is Simple Random Sampling. Respondents in the intervention group were given peer education related to BSE with the help of modules. Research data processing uses SPSS with Wilcoxon and Mann-Whitney. This research has been declared ethically appropriate for research with number 030/EC-KEPK FKIK UMY/I/2024. The results of the study showed that there was a difference in pretest-posttest knowledge scores of 0.014 (p<0.05) in the intervention group and there was no difference in results in the control group with a result of 0.257 (p>0.05). Differences in pretest-posttest skill scores occurred in the intervention and control groups with sequential results of 0.001 (p<0.05), and 0.014 (p<0.05). The comparison of posttest knowledge and skills scores between the intervention and control groups respectively was 0.001 and 0.003 (p<0.05). Based on the result peer education is effective in improving teenagers' knowledge and skills related to BSE so that it can be used as an educational method related to BSE.